1999
DOI: 10.1063/1.124612
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index and hygroscopic stability of AlxGa1−xAs native oxides

Abstract: We present prism coupling measurements on AIXGal.XAs native oxides showing the dependent~~c E!vE'D refractive index on composition (0.3 SXS0.97), oxidation temperature (400q<500), and carrier g purity. Index values range from n=l .490 (x=O.9, 400 "C) to 1.707 (x=O.3, 500 "C). The oxides are *)Electronicmail: dhall(j?nd.edu Sandia is a multiprogram laboratory operated by Sandia Corporation, a Lockheed Martin Company, for the United States Department of Energy under Contract DE-AC04-04AL85000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Optical properties of AlOx have been characterized with discrepancies in the published results. AlOx transparency region has been unambiguously demonstrated to extend from deep UV (about 240 nm) up to 10 m, Hall et al, 1999) excepted an O-H absorption peak that we identified at 3 m (Ravaro et al, 2008). However several different values of the AlOx refractive index have been reported.…”
Section: Selective Oxidationmentioning
confidence: 85%
See 1 more Smart Citation
“…Optical properties of AlOx have been characterized with discrepancies in the published results. AlOx transparency region has been unambiguously demonstrated to extend from deep UV (about 240 nm) up to 10 m, Hall et al, 1999) excepted an O-H absorption peak that we identified at 3 m (Ravaro et al, 2008). However several different values of the AlOx refractive index have been reported.…”
Section: Selective Oxidationmentioning
confidence: 85%
“…In the NIR these are included between 1.55 and 1.64, with a claimed dependence on the original Al composition. (Knopp et al, 1998;Hall et al, 1999;Durand et al, 2003) This is a major issue for the design of birefringent GaAs/AlOx nonlinear waveguides, as uncertainty on these properties affects the phase-matching wavelength of such devices. Selective oxidation of GaAs/AlAs waveguides is carried out in a quartz tube oven where samples are heated at 420-430°C while the atmosphere is saturated in water vapor by a 2 l/min flux of wet N 2 .…”
Section: Selective Oxidationmentioning
confidence: 99%
“…16 In general, conventional wet oxides of low Al-content AlGaAs are of inferior quality to those grown via O 2 -enhanced wet oxidation, as indicated by greater dissolution in the stain etch seen in Fig. 1͑a͒, much lower refractive index ͑1.45-1.5 vs 1.65-1.7͒, 15,17 and poorer adhesion. 16 While the images in Fig.…”
Section: Reduction Of Etched Algaas Sidewall Roughness By Oxygen-enhamentioning
confidence: 94%
“…In particular, the presence of dilute O 2 during wet oxidation significantly increases the refractive index of Al 0.3 Ga 0.7 As from n ϳ 1.48 ͑no O 2 added͒ to n ϳ 1.68 ͑4000-7000 ppm O 2 ͒. 5,13 After cap layer removal, both the Al 0.3 Ga 0.7 As and Al 0.85 Ga 0.15 As layers are fully oxidized from the surface, resulting in an oxide single heterostructure planar waveguide. Details of the nonselective O 2 -enhanced wet oxidation process used in this work can be found in Ref.…”
mentioning
confidence: 97%
“…5,6 Figure 1 shows a transverse electric ͑TE͒ prism coupling mode profile measured at 633 nm for the 1 m guiding layer structure after oxidizing for 88 min at 450°C with the addition of 7000 ppm O 2 ͑relative to the N 2 carrier gas͒. The waveguide structure schematic inset in Fig.…”
mentioning
confidence: 98%